THE USAGE OF FUTURE SIMPLE TENSE - Muxammadiyev Aziz Shavkatovich, Suyunov Javohir Shokir o‘g‘li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This article deal with the importance of future simple tense mistakes and this article is important in solving grammar mistakes in the future tense.